Reduced shoulder proprioception due to fatigue after repeated handball throws and evaluation of test-retest reliability of a clinical shoulder joint position test - Sutton, P.; Lund Ohlsson, M.; Röijezon, U. (Shoulder & Elbow, 2022)
Background: Proprioception is vital for motor control and can be disturbed, for example, due to fatigue or injury. Clinical feasible, reliable and valid tests of shoulder proprioception are warranted. The aim was to investigate the effects of local fatigue on shoulder proprioception and the reliability of a feasible joint position sense test using an experimental repeated measures design. Method: Forty participants repeated a shoulder joint position sense test to assess test-retest reliability. The test was then utilized on a subgroup of handball players who were subjected to five bouts of a repeated throwing task with the dominant hand. The effect of local fatigue was investigated by comparing the fatigued with the non-fatigued shoulder. Results: There was a significant interaction for the arm × bout (p = 0.028, ?p2 = 0.20) and a significant effect for the arm (p = 0.034, ?p2 = 0.35) with a significant decrease in joint position sense for the throwing arm compared to the non-throwing arm. The intraclass correlation coefficient was 0.78 (95% CI = [0.57; 0.89]). The standard error of measurement between trials was 0.70° (range: 0.57°-0.90°). Discussion: The results indicate that repeated throwing to fatigue disturbs shoulder joint position sense. Assessment with the modified test showed acceptable reliability and can be a valuable assessment tool in the clinic.